(untitled) (Anclajes, 2019)
This article aims at defining what we understand by a gay cultural subjectivity, and endeavours to apply this concept to the experience that an effeminate proto-homosexual child experiences when building his own subjectivity which starts from the difference. In other words, we mean a subjectivity that inscribes him in a marginal alterity. Next, the article reviews the manner in which this theoretical view has crystallized in the work of some Latin American authors towards the figure of the "loca", to focus more specifically on the character of Toto, Manuel Puig’s autofictional mask in The Betrayal of Rita Hayworth (1968). We conclude by proposing, from the queer Utopia, a path able to deactivate what Michel Foucault calls "disciplination of bodies" imposed by biopolitics.